HIV-1-Associated Neurocognitive Disorders: Is HLA-C Binding Stability to β2-Microglobulin a Missing Piece of the Pathogenetic Puzzle? - Zipeto, Donato; Serena, Michela; Mutascio, Simona; Parolini, Francesca; Diani, Erica; Guizzardi, Elisabetta; Muraro, Valentina; Lattuada, Emanuela; Rizzardo, Sebastiano; Malena, Marina; Lanzafame, Massimiliano; Malerba, Giovanni; et al. (Frontiers in Neurology, 2018)
AIDS dementia complex (ADC) and HIV-associated neurocognitive disorders (HAND) are complications of HIV-1 infection. Viral infections are risk factors for the development of neurodegenerative disorders. Aging is associated with low-grade inflammation in the brain, i.e., the inflammaging. The molecular mechanisms linking immunosenescence, inflammaging and the pathogenesis of neurodegenerative disorders, such as Alzheimer’s disease (AD) and Parkinson’s disease, are largely unknown. ADC and HAND share some pathological features with AD and may offer some hints on the relationship between viral infections, neuroinflammation, and neurodegeneration. β2-microglobulin (β2m) is an important pro-aging factor that interferes with neurogenesis and worsens cognitive functions. Several studies published in the 80s-90s reported high levels of β2m in the cerebrospinal fluid of patients with ADC. High levels of β2m have also been detected in AD. Inflammatory diseases in elderly people are associated with polymorphisms of the MHC-I locus encoding HLA molecules that, by associating with β2m, contribute to cellular immunity. We recently reported that HLA-C, no longer associated with β2m, is incorporated into HIV-1 virions, determining an increase in viral infectivity. We also documented the presence of HLA-C variants more or less stably linked to β2m. These observations led us to hypothesize that some variants of HLA-C, in the presence of viral infections, could determine a greater release and accumulation of β2m, which in turn, may be involved in triggering and/or sustaining neuroinflammation. ADC is the most severe form of HAND. To explore the role of HLA-C in ADC pathogenesis, we analyzed the frequency of HLA-C variants with unstable binding to β2m in a group of patients with ADC. We found a higher frequency of unstable HLA-C alleles in ADC patients, and none of them was harboring stable HLA-C alleles in homozygosis. Our data suggest that the role of HLA-C variants in ADC/HAND pathogenesis deserves further studies. If confirmed in a larger number of samples, this finding may have practical implication for a personalized medicine approach and for developing new therapies to prevent HAND. The exploration of HLA-C variants as risk factors for AD and other neurodegenerative disorders may be a promising field of study.